STRATEGI KOMUNIKASI KETUA LAZISNU MWCNU PESANGGARAN DALAM MENINGKATKAN MOTIVASI KERJA ANGGOTA - Moh. Muslimin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
An organization always strives to create a harmonious working relationship between leaders and members, to maintain these conditions a leader is needed who can have a great influence and can motivate members to work, in order to optimize their performance. An effective leader must be able to provide direction, evaluation, and correction of the efforts made by members in achieving organizational goals. The focus of this research is on